LCT-3d Induces Oxidative Stress-Mediated Apoptosis by Upregulating Death Receptor 5 in Gastric Cancer Cells - Wang, Menglin; Wu, Xinxin; Yu, Lu; Hu, Zi-yun; Li, Xiaobo; Meng, Xia; Lv, Chun-tao; Kim, Gi-Young; Choi, Yung Hyun; Wang, Zhengya; Xu, Hai-Wei; Jin, Cheng-Yun (Frontiers in Oncology, 2021)
Gastric cancer is a global health problem. In this study, we investigate the role of a novel Indole derivative, named LCT-3d, in inhibiting the growth of gastric cancer cells by MTT assay. The Western blotting results showed that LCT-3d modulated the mitochondrial-related proteins and Cleaved-Caspases 3/9, to induce cell apoptosis. The up-regulation of Death receptor 5 (DR5) in MGC803 cells was observed with LCT-3d treatment. Knockdown of DR5 on MGC803 cells partially reversed the LCT-3d-induced mitochondrial apoptosis. The level of Reactive Oxygen Species (ROS) in MGC803 cells was increased with LCT-3d treatment and could be blocked with the pretreatment of the ROS inhibitor N-Acetylcysteine (NAC). The results demonstrate that the elevating ROS can up-regulate the expression of DR5, resulting in apoptosis via mitochondrial pathway. Although the nuclear factor erythroid-2 related factor 2 (Nrf2) pathway served an important role in protecting gastric cancer cells against the injury of ROS, it can’t reverse LCT-3d-induced cell apoptosis. Taken together, our study showed that LCT-3d induced apoptosis via DR5-mediated mitochondrial apoptotic pathway in gastric cancer cells. LCT-3d could be a novel lead compound for development of anti-cancer activity in gastric cancer.